2018
DOI: 10.1177/2325967118769328
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Return to Sport After Ulnar Collateral Ligament Reconstruction in Adolescent Baseball Players

Abstract: Background:The number of ulnar collateral ligament (UCL) reconstructions in adolescent athletes has increased over the past 2 decades. Clinical results in this population have not been well studied.Purpose/Hypothesis:The purpose of this study was to evaluate the outcomes and return to sport after UCL reconstruction in a large group of adolescent baseball players. We hypothesized that excellent clinical outcomes and high rates of return to sport would be observed in this population at a minimum 2-year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 33 publications
2
73
0
Order By: Relevance
“…RTP time was reported for the docking technique in 3 articles 29,30,35 and for the figure-of-8 studies technique (all modified Jobe) in 4 articles. 10,17,39,44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RTP time was reported for the docking technique in 3 articles 29,30,35 and for the figure-of-8 studies technique (all modified Jobe) in 4 articles. 10,17,39,44…”
Section: Resultsmentioning
confidence: 99%
“…Routine ulnar nerve transposition for all patients was reported in 9 studies utilizing the figure-of-8 technique—subcutaneously in 7 studies 1,3,10,17,34,37,39 and submuscularly in 2 studies. 13,28 No authors reported routine ulnar nerve transposition for patients in whom a docking reconstruction was performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, most of them assess activities of daily living (ADL) whereas high-functioning overhead athletes often only notice symptoms or discomfort during sport-specific loading (Gallagher et al, 2017). The Kerlan-Jobe Orthopedic Clinic (KJOC) Shoulder and Elbow Score (Alberta et al, 2010) is one of the most widely used, valid, and reliable clinical outcome measures that is specific to the shoulder and elbow joint in overhead athletes (Merolla, Paladini, and Porcellini, 2018;Peduzzi et al, 2019;Saper et al, 2018). The KJOC is a patient-administered questionnaire consisting of 10 items to measure the functional status of the upper extremity in this high-functioning population.…”
Section: Introductionmentioning
confidence: 99%
“…18,22,23,38,44 While this return-to-play (RTP) rate is quite favorable, the mean time to RTP is 12 to 18 months. 6,7,13,27,46 This extended time frame is problematic for patients, as they miss at least 1 full season of play and often miss 2 full seasons following surgery. Additionally, Erickson et al 21 demonstrated that there is no significant difference in the time to return to sport between professional baseball pitchers who required a revision UCL reconstruction and those who did not.…”
mentioning
confidence: 99%